Modelling the stand dynamics after a thinning induced partial mortality: A compensatory growth perspective - Li, Chao; Barclay, Hugh; Huang, Shongming; Roitberg, Bernard; Lalonde, Robert; Xu, Wenli; Chen, Yingbing (Frontiers in Plant Science, 2022)
With increasing forest areas under management, dynamics of managed stands have gained more attention by forest managers and practitioners. Improved understanding on how trees and forest stands would respond to different disturbances is required to predict the dynamics of managed stands. Partial mortality commonly occurs in stand development, and different response patterns of trees and stands to partial mortality would govern stand dynamics. To investigate the possible response patterns using existing knowledge of growth and yield relationships, we developed TreeCG model, standing for Tree’s Compensatory Growth, a state-dependent individual tree-based forest growth model that simulates the compensatory growth of trees after experiencing a partial mortality. The mechanism behind the simulation is the redistribution of resources, including nutrients and space, freed from died trees to surviving trees. The developed new algorithm simplified the simulations of annual growth increments of individual trees over a long period of stand development. The model was able to reproduce the forest growth patterns displayed in long-term precommercial thinning experiments. The simulated forest growth displayed the process of compensatory growth from under compensation, to compensation-induced-equality, and to overcompensation over time. Our model can simulate stand growth trajectories after different partial harvest regimes at different times and intensities, thus support decisions in best partial harvest strategies. This generic model can be refined with given tree species and specific site conditions to predict stand dynamics after given partial mortality for any jurisdictions under management. The simulation reassembles growth trajectories of natural stands when no thinning is conducted.